Preparation method and application of AIEgen type self-assembled hole transport material

By using AIEgen self-assembled hole transport materials in perovskite solar devices, the problem of self-assembled small molecule materials being easily decomposed under ultraviolet light is solved, and an efficient and stable hole transport layer is achieved, which improves perovskite Performance and stability of solar devices.

CN119119121AActive Publication Date: 2024-12-13GUANGXI UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411205837.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2024-12-13
Estimated Expiration
2044-08-30

AI Technical Summary

Technical Problem

The existing self-assembled small molecule materials are prone to accelerate decomposition under ultraviolet light, resulting in insufficient stability and film formation uniformity of perovskite solar devices, affecting device performance and long-term use.

Method used

Using AIEgen self-assembled hole transport material, with a specific structure, it is synthesized through a simple preparation method without strict water and oxygen-free conditions, and is used for the hole transport layer of trans perovskite solar devices to improve the stability of the device. Sex and efficiency.

Benefits of technology

A dense and uniform hole transport layer is realized, which reduces the damage of ultraviolet rays to perovskite solar devices, improves the stability and efficiency of the device, and promotes the development of photovoltaic technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119121A_ABST
    Figure CN119119121A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of an AIEgen type self-assembled hole transport material, the AIEgen type self-assembled hole transport material has a structure shown in a general formula (I) or a general formula (II): # imgabs0 #, in which L1 and L2 are independently selected from C2, C3, C4, C5 or C6 linear alkyl; r1, R2, R3 and R4 are independently selected from-H,-Br,-CF3, methyl, methoxyl, hydroxyl, amino, phenyl or carboxylic acid group. The self-assembled hole transport material is used in a perovskite solar device so as to improve the efficiency of the device and improve the stability; the compact and uniform hole transport layer is obtained, defects are effectively passivated, non-radiation convergence is reduced, and the performance of the device is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of solar device materials, and in particular relates to a preparation method and application of an AIEgen type self-assembled hole transport material. Background Art

[0002] Perovskite solar cells have become the most competitive technology in the next generation of photovoltaic technology due to their breakthroughs in efficiency, stability and cost-effectiveness. The structure of a formal perovskite solar device is, from bottom to top, a transparent conductive substrate, an electron transport layer, a perovskite active layer, a hole transport layer, and an electrode. In a trans-perovskite solar device, the positions of the electron transport layer and the hole transport layer are interchanged, and the rest of the structure remains unchanged. Trans-perovskite solar devices have become the focus of research by scientific researchers due to their simple preparation process, high stability, low-temperature preparation, and suitability for the preparation of stacked cells. Currently, commonly used hole transport materials include polymers such as PTAA, inorganic semiconductor materials such as NiOX, and organic small molecule materials such as self-assembled molecules (SAMs). Among them, SAMs are expected to become the hope for promoting the further development of perovskite solar devices due to their low cost, simple structure, adjustable energy levels, and easy modification.

[0003] Self-assembled molecules (SAMs) play an important role as selective contact points in solar cells, determining the performance and stability of these photovoltaic devices. Currently, research on self-assembled molecules is mainly focused on improving efficiency and stability. However, devices prepared by self-assembled small molecules will accelerate decomposition under ultraviolet light, which is not conducive to the long-term stability required by solar devices. In addition, there are shortcomings such as insufficient film uniformity and poor growth of perovskite crystals. Summary of the invention

[0004] The purpose of the present invention is to provide a preparation method and application of an AIEgen type self-assembled hole transport material, which is used in perovskite solar devices to improve device efficiency and enhance stability; a dense and uniform hole transport layer is obtained, defects are effectively passivated, non-radiative convergence is reduced, device performance is improved, and stability is optimized.

[0005] The present invention adopts the following technical solution: AIEgen type self-assembled hole transport material has a structure shown in general formula (I) or general formula (II):

[0006]

[0007] Wherein, L1 and L2 are independently selected from a linear alkyl group of C2, C3, C4, C5 or C6;

[0008] R1, R2, R3, and R4 are independently selected from -H, -Br, -CF3, methyl, methoxy, hydroxy, amino, phenyl, or carboxylic acid.

[0009] Furthermore, L1 and L2 independently select one of the following:

[0010]

[0011] The present invention also discloses a method for preparing the above-mentioned AIEgen type self-assembled hole transport material. The preparation process of the self-assembled hole transport material having a structure shown in general formula (I) is as follows:

[0012]

[0013] The preparation process of the self-assembled hole transport material of the structure shown in general formula (II) is as follows:

[0014]

[0015] The present invention also discloses the use of the above-mentioned AIEgen type self-assembled hole transport material, which is used for preparing an inverse perovskite solar device.

[0016] The present invention also discloses an inverse perovskite solar device, which is based on the above-mentioned AIEgen type self-assembled hole transport material, which is used for the hole transport layer, and from bottom to top are a transparent conductive substrate, a hole transport layer, an active layer, an electron transport layer and an electrode.

[0017] The beneficial effects of the present invention are as follows: 1. The preparation method is simple in steps, and the reaction between borate and bromine can be achieved without adding water and subsequent complicated post-treatment. The synthesis steps do not require strict anhydrous and oxygen-free conditions to obtain the target molecule with high yield, which is highly feasible and is expected to be applied on a large scale. 2. By absorbing ultraviolet rays, the damage to perovskite solar devices is reduced, and the stability and efficiency of perovskite solar devices are further improved, promoting the development of photovoltaic technology. 3. A dense hole transport layer is obtained in the process of preparing the device, which is conducive to achieving a uniform perovskite layer with high film quality. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 is the H NMR spectrum of the compound of formula 9;

[0019] Figure 2 is the C NMR spectrum of the compound of formula 9;

[0020] Figure 3 is the H NMR spectrum of the compound of formula 25;

[0021] Figure 4 is the C NMR spectrum of the compound of formula 25;

[0022] Figure 5 The UV-visible diffuse reflectance spectra of the compounds of formula 9, 25, and 4PACz dissolved in ethanol;

[0023] Figure 6 is a JV curve of a perovskite solar device using the compound of formula 9;

[0024] Figure 7 is the JV curve of the perovskite solar device using the compound of formula 25;

[0025] Figure 8 The fluorescence spectra of the compound of formula 25 under different volume fractions of THF / H2O. DETAILED DESCRIPTION

[0026] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0027] The present invention discloses an AIEgen type self-assembled hole transport material having a structure shown in general formula (I) or general formula (II):

[0028]

[0029]

[0030] Wherein, L1 and L2 are selected from C2, C3, C4, C5 or C6 straight chain alkyl groups;

[0031] R1, R2, R3, R4 are independently selected from -H, -Br, -CF3, methyl, methoxy, hydroxyl, amino, phenyl or carboxylic acid;

[0032] The structure of phosphate is as follows:

[0033]

[0034] Wherein, "*" represents the connection position between the acid radical structure and the alkyl chain of general formula (I) or (II).

[0035] L1 and L2 independently select one of the following:

[0036]

[0037] The specific molecular structure of the self-assembled hole transport material is as follows:

[0038]

[0039]

[0040]

[0041] The invention also discloses that the self-assembled hole transport material is used to prepare an inverse perovskite solar device.

[0042] An inverse perovskite solar device, wherein the self-assembled hole transport material is used for the hole transport layer, which comprises, from bottom to top, a transparent conductive substrate, a hole transport layer, an active layer, an electron transport layer and an electrode.

[0043] Example 1

[0044] Formula (1) Synthesis process of self-assembling molecules:

[0045]

[0046] Synthesis of compound of formula (1-2):

[0047] Under nitrogen atmosphere, a dry round-bottom flask equipped with a stirring magnet was added with the compound of formula (1-1) (1.00 g, 3.41 mmol, 1 eq), triphenylethylene bromide (1.14 g, 3.41 mmol, 1 eq.), Pd-P(t-Bu)3-G4 (111.2 mg, 0.17 mmol, 5.0 mol%), potassium trimethylsilanol (481.1 mg, 3.75 mmol, 1.1 eq.) and toluene (20 mL), and the reaction mixture was stirred at 45° C. for 15 hours. The crude product was purified by column chromatography (PE:DCM 2:1 v:v) to give 1.21 g of white crystals with a yield of 86%.

[0048] Synthesis of compound of formula (1-3):

[0049] The compound of formula (1-2) (1.00 g, 2.37 mmol, 1 eq) was dissolved in 1,4-dibromoethane (5 mL, 47.4 mmol, 20 eq), and tetrabutylammonium bromide (118.7 mg, 0.36 mmol, 0.15 eq) and 50% KOH aqueous solution (664.9 mg, 1.4 ml, 11.85 mmol, 5 eq) were added under a nitrogen atmosphere. The mixture was heated to 65 ° C and stirred overnight. After the reaction was completed, the reactant was extracted with dichloromethane. The organic layer was dried over anhydrous Na2SO4 and the solvent was removed under reduced pressure. The crude product was purified by column chromatography (PE: DCM4: 1 v: v) to give 890.1 mg of a white solid with a yield of 69.0%.

[0050] Synthesis of compound of formula (1-4):

[0051] Under nitrogen atmosphere, 1-3 (800 mg, 1.51 mmol, 1 eq) was dissolved in triethyl phosphite (5.0 mL, 28.8 mmol, 20 eq) and then stirred at 145 ° C for 15 hours. After the reaction was completed, the solvent was distilled off under reduced pressure. The crude product was purified by column chromatography (DCM) to give 750.4 mg of off-white solid with a yield of 89%.

[0052] Synthesis of compound of formula (1):

[0053] Under nitrogen atmosphere, the compound of formula (1-4) (292.8 mg, 0.5 mmol, 1 eq) was dissolved in anhydrous 1,4-dioxane (6 mL), and bromotrimethylsilane (10 eq, 0.66 mL, 5 mmol) was added dropwise. The reaction was stirred at room temperature for 12 hours. The solvent was then partially distilled off under reduced pressure, and the liquid residue was dissolved in methanol (3 ml). Next, the liquid was poured into distilled water (30 ml). The product was then filtered and washed with water to obtain 150.6 mg of off-white solid with a yield of 56.9%.

[0054] Example 2

[0055] The synthesis process of self-assembling molecules of formula (17):

[0056]

[0057] Synthesis of compound of formula (17-2):

[0058] Under nitrogen atmosphere, formula (17-1) (1.00 g, 3.41 mmol, 1 eq), 1-(4-bromophenyl)-1,2,2-triphenylethylene (1.40 g, 3.41 mmol, 1 eq), Pd-P(t-Bu)3-G4 (111.2 mg, 0.17 mmol, 5.0 mol%), potassium trimethylsilanol (481.1 mg, 3.75 mmol, 1.1 eq.) and toluene (20 mL) were added to a dry round-bottom flask equipped with a stirring magnetic bar, and the reaction mixture was stirred at 45° C. for 15 hours. The crude product was purified by column chromatography (PE:DCM 2:1 v:v) to obtain 1.53 g of white crystals with a yield of 84%.

[0059] Synthesis of compound of formula (17-3):

[0060] The compound of formula (17-2) (1.00 g, 2.01 mmol, 1 eq) was dissolved in 1,4-dibromoethane (5 mL, 47.4 mmol, 20 eq), and tetrabutylammonium bromide (97.2 mg, 0.30 mmol, 0.15 eq) and 50% KOH aqueous solution (563.9 mg, 1.13 ml, 10.05 mmol, 5 eq) were added under a nitrogen atmosphere. The mixture was heated to 65 ° C and stirred overnight. After the reaction was completed, the reactant was extracted with dichloromethane. The organic layer was dried over anhydrous Na2SO4 and the solvent was removed under reduced pressure. The crude product was purified by column chromatography (PE: DCM 4: 1 v: v) to give 896.3 mg of a white solid with a yield of 73.8%.

[0061] Synthesis of compound of formula (17-4):

[0062] Under nitrogen atmosphere, formula (17-3) (800 mg, 1.32 mmol, 1 eq) was dissolved in triethyl phosphite (4.5 mL, 26.4 mmol, 20 eq), and then stirred at 145 ° C for 15 hours. After the reaction was completed, the solvent was distilled off under reduced pressure. The crude product was purified by column chromatography (DCM) to obtain 760.6 mg (87%) of off-white solid.

[0063] Synthesis of compound of formula (17):

[0064] Under nitrogen atmosphere, the compound of formula (17-4) (330.89 mg, 0.5 mmol, 1 eq) was dissolved in anhydrous 1,4-dioxane (6 mL), and bromotrimethylsilane (10 eq, 0.66 mL, 5 mmol) was added dropwise. The reaction was stirred at room temperature for 12 hours. The solvent was then partially distilled off under reduced pressure, and the liquid residue was dissolved in methanol (3 ml). Next, the liquid was poured into distilled water (30 ml). The product was then filtered and washed with water to obtain 162.1 mg of off-white solid with a yield of 53.5%.

[0065] Example 3

[0066] Formula (9) Synthesis process of self-assembling molecules:

[0067]

[0068] Synthesis of compound of formula (9-2):

[0069] Under nitrogen atmosphere, formula (9-1) (1.00 g, 3.41 mmol, 1 eq), triphenylethylene bromide (1.14 g, 3.41 mmol, 1 eq.), Pd-P(t-Bu)3-G4 (111.2 mg, 0.17 mmol, 5.0 mol%), potassium trimethylsilanol (481.1 mg, 3.75 mmol, 1.1 eq.) and toluene (20 mL) were added to a dry round-bottom flask equipped with a stirring magnet, and the reaction mixture was stirred at 45° C. for 15 hours. The crude product was purified by column chromatography (PE: DCM 2:1 v:v) to give 1.25 g of white crystals with a yield of 87%.

[0070] Synthesis of compound of formula (9-3):

[0071] The compound of formula (9-2) (1.00 g, 2.37 mmol, 1 eq) was dissolved in 1,4-dibromobutane (5.7 mL, 47.4 mmol, 20 eq), and tetrabutylammonium bromide (118.7 mg, 0.36 mmol, 0.15 eq) and 50% KOH aqueous solution (664.9 mg, 1.4 ml, 11.85 mmol, 5 eq) were added under a nitrogen atmosphere. The mixture was heated to 65 ° C and stirred overnight. After the reaction was completed, the reactant was extracted with dichloromethane. The organic layer was dried over anhydrous Na2SO4 and the solvent was removed under reduced pressure. The crude product was purified by column chromatography (PE: DCM 4: 1 v: v) to give 976.1 mg of a white solid with a yield of 74.0%.

[0072] Synthesis of compound of formula (9-4):

[0073] Under nitrogen atmosphere, 9-3 (800 mg, 1.44 mmol, 1 eq) was dissolved in triethyl phosphite (5.0 mL, 28.8 mmol, 20 eq) and then stirred at 145 ° C for 15 hours. After the reaction was completed, the solvent was distilled off under reduced pressure. The crude product was purified by column chromatography (DCM) to give 795.8 mg (92%) of off-white solid.

[0074] Synthesis of self-assembling molecules of formula (9):

[0075] Under a nitrogen atmosphere, compound 9-4 (306.9 mg, 0.5 mmol, 1 eq) was dissolved in anhydrous 1,4-dioxane (6 mL), and bromotrimethylsilane (10 eq, 0.66 mL, 5 mmol) was added dropwise. The reaction was stirred at room temperature for 12 hours. The solvent was then partially distilled off under reduced pressure, and the liquid residue was dissolved in methanol (3 ml). Next, the liquid was poured into distilled water (30 ml). The product was then filtered and washed with water to obtain 164.5 mg of off-white solid with a yield of 59%. Figure 1As shown, the measured self-assembly molecule of formula 9 1 H NMR spectrum, integrated analysis, 1H NMR (600MHz, DMSO) δ7.85 (d, J = 7.3Hz, 1H), 7.71 (s, 1H), 7.56 (d, J = 7.8Hz, 1H), 7.40-7.37 (m, 1H), 7.13-7.00 (m, 9H), 4.30 (s, 2H), 1.79 (s, 1H), 1.53 (s, 3H). 13C NMR (151MHz, DMSO) δ131.27 (d, J = 9.7 Hz, 1H), 128.25 (d, J = 3.9 Hz, 1H), 40.41 (s, 6H), 40. 27(s,22H),40.13(s,22H),39.99(s,32H),39.85(s,25H),39.71(s,19H),39.57(s,5H). Figure 2 The 13C NMR spectrum of the self-assembled molecule of formula 9 was measured, and the integral analysis was performed to obtain 13C NMR (151 MHz, DMSO) δ131.27 (d, J = 9.7 Hz, 1H), 128.25 (d, J = 3.9 Hz, 1H), 40.41 (s, 6H), 40.27 (s, 22H), 40.13 (s, 22H), 39.99 (s, 32H), 39.85 (s, 25H), 39.71 (s, 19H), 39.57 (s, 5H). In summary, the self-assembled molecule of formula (9) was prepared by the above method.

[0076] Example 4

[0077] The synthesis process of the self-assembling molecule of formula (25):

[0078]

[0079] Synthesis of compound of formula (25-2):

[0080] Under nitrogen atmosphere, formula (25-1) (1.00 g, 3.41 mmol, 1 eq), 1-(4-bromophenyl)-1,2,2-triphenylethylene (1.40 g, 3.41 mmol, 1 eq), Pd-P(t-Bu)3-G4 (111.2 mg, 0.17 mmol, 5.0 mol%), potassium trimethylsilanol (481.1 mg, 3.75 mmol, 1.1 eq.) and toluene (20 mL) were added to a dry round-bottom flask equipped with a stirring magnet, and the reaction mixture was stirred at 45° C. for 15 hours. The crude product was purified by column chromatography (PE:DCM 2:1 v:v) to give 1.41 g of white crystals with a yield of 83%.

[0081] Synthesis of compound of formula (25-3):

[0082] The compound of formula (25-2) (1.00 g, 2.01 mmol, 1 eq) was dissolved in 1,4-dibromobutane (4.8 mL, 40.2 mmol, 20 eq), and tetrabutylammonium bromide (97.2 mg, 0.30 mmol, 0.15 eq) and 50% KOH aqueous solution (563.9 mg, 1.13 ml, 10.05 mmol, 5 eq) were added under nitrogen atmosphere. The mixture was heated to 65 ° C and stirred overnight. After the reaction was completed, the reactant was extracted with dichloromethane. The organic layer was dried over anhydrous Na2SO4 and the solvent was removed under reduced pressure. The crude product was purified by column chromatography (PE: DCM 4: 1 v: v) to give 919.4 mg of a white solid with a yield of 72.3%.

[0083] Synthesis of compound of formula (25-4):

[0084] Under nitrogen atmosphere, 25-3 (800 mg, 1.26 mmol, 1 eq) was dissolved in triethyl phosphite (4.34 mL, 25.3 mmol, 20 eq) and then stirred at 145 ° C for 15 hours. After the reaction was completed, the solvent was distilled off under reduced pressure. The crude product was purified by column chromatography (DCM) to give 782.3 mg of off-white solid with a yield of 90%.

[0085] Synthesis of self-assembling molecules of formula (25):

[0086] Under nitrogen atmosphere, compound 25-4 (344.9 mg, 0.5 mmol, 1 eq) was dissolved in anhydrous 1,4-dioxane (6 mL), and bromotrimethylsilane (10 eq, 0.66 mL, 5 mmol) was added dropwise. The reaction was stirred at room temperature for 12 hours. The solvent was then partially distilled off under reduced pressure, and the liquid residue was dissolved in methanol (3 ml). Next, the liquid was poured into distilled water (30 ml). The product was then filtered and washed with water to obtain 177.4 mg (56%) of off-white solid.

[0087] The self-assembled molecules of formula 25 prepared in Example 4 were tested using a Bruker AVANCE III HD600 MHz spectrometer using DMSO-d6 as solvent. 1 H NMR spectra and 13 C NMR spectrum.

[0088] Figure 3 is the measured self-assembled molecule of formula 25 1H NMR spectrum, analyzed, obtained 1H NMR (600MHz, DMSO) δ8.44 (d, J = 1.5Hz, 1H), 8.22 (d, J = 7.7Hz, 1H), 7.71 (dd, J = 8.6, 1.7Hz, 1H), 7.66–7.56 (m, 5H), 7.45 (t, J = 7.6Hz, 1H), 7.21–7.16 (m, 5H), 7.16–7.12 (m, 5H), 7.07–7.03 (m, 5H), 7.00–6.98 (m, 2H), 4.40 (t, J = 7.0Hz, 2H), 3.57 (s, 2H), 1.88–1.83 (m, 2H), 1.55–1.51 (m, 4H); Figure 4 is the measured self-assembled molecule of formula 25 13 C NMR spectrum, integrated analysis, obtained 13C NMR (151MHz, DMSO) δ 131.19 (d, J = 11.0Hz, 1H), 128.70-128.21 (m, 1H), 40.41 (s, 6H), 40.20 (d, J = 21.0Hz, 29H), 40.01 (s, 18H), 39.99 (s, 37H), 39.85 (s, 19H), 39.71 (s, 14H), 39.57 (s, 4H). The self-assembling molecule of formula 25 was synthesized by the above method.

[0089] Optical performance test:

[0090] The UV-visible absorption spectra of the self-assembly molecules of formula 9 and 25 prepared in Example 3 and Example 4 and the commonly used self-assembly molecule 4PACz in solution were tested using a UV-visible spectrophotometer, and the optical band gap was calculated using the empirical formula Eg=1240 / λ absorption margin. 10-5mol / L of the self-assembly molecules of formula 9, 25 and 4PACz dissolved in ethanol were prepared respectively for UV-visible spectrophotometer testing and analysis, and the following results were obtained: Figure 5 The UV-visible absorption spectra are shown in Table 1, and the optical performance parameters of the self-assembled molecules of Formula 9 and 25 are obtained. Figure 5 As shown in Table 1, the peak value of the self-assembled molecule of formula 25 is the largest, followed by the self-assembled molecule of formula 9 and 4PACz. The conventional self-assembled molecule 4PACz has the weakest absorption of ultraviolet light. Therefore, it can be seen that after the introduction of molecules with AIE properties, the absorption of ultraviolet light by the hole transport layer is enhanced. It can be inferred that the self-assembled molecule of formula 25 can effectively prevent ultraviolet rays from damaging perovskite solar cells, and the ultraviolet absorption of AIEgen self-assembled molecules is stronger than that of conventional self-assembled molecule 4PACz.

[0091] Table 1 Optical performance parameter test results

[0092] Self-assembling molecules Band Gap Formula 9 3.84eV Formula 25 3.86eV

[0093] Device performance test:

[0094] The perovskite solar devices were prepared using the self-assembled hole transport materials of formula 9 and formula 25, and tested. Figure 6 and Figure 7 As shown. In the process of preparing perovskite solar devices, a dense hole transport layer, a uniform perovskite layer and high film quality were observed. Figure 6 and Figure 7 The JV curves of Equation 9 and Equation 25 when used as hole transport layers in perovskite solar devices are shown in the figure. As can be seen from the figure, both of them have achieved high open circuit voltages, 1.81V for Equation 9 and 1.83 for Equation 25. Therefore, the prepared self-assembled molecules with AIE properties can be used as efficient hole transport layers for perovskite solar devices.

[0095] AIE performance test:

[0096] The photoluminescence (PL) behavior of the self-assembled molecule of formula 25 prepared in Example 4 in different volume fractions of tetrahydrofuran / water was studied by steady-state fluorescence measurement. Figure 8 It can be seen that when tetrahydrofuran is not added, the self-assembled molecule of formula 25 has almost no fluorescence in aqueous solution, that is, the self-assembled molecule of formula 25 has basically no fluorescence in aqueous solution, but as the content of the poor solvent tetrahydrofuran increases from 0% to 90%, aggregates are formed, and the luminescence of the entire system is enhanced. The results show that the self-assembled molecule of formula 25 and the AIEgen self-assembled hole transport material with the structure shown in general formula (I) or general formula (II) have AIE characteristics. The self-assembled molecules with AIE properties have stronger absorption of ultraviolet light, which is beneficial to the long-term stability of perovskite solar devices; and the absorbed ultraviolet light can be converted into visible light, thereby improving the utilization rate of sunlight.

Claims

1. AIEgen type self-assembled hole transport material, characterized in that Having the structure shown by general formula (I) or general formula (II): Wherein, L1 and L2 are independently selected from a linear alkyl group of C2, C3, C4, C5 or C6; R1, R2, R3, and R4 are independently selected from -H, -Br, -CF3, methyl, methoxy, hydroxy, amino, phenyl, or carboxylic acid.

2. The AIEgen type self-assembled hole transport material according to claim 1, characterized in that: L1 and L2 independently select one of the following:

3. The method for preparing the AIEgen type self-assembled hole transport material according to claim 1 or 2, characterized in that: The preparation process of the self-assembled hole transport material of the structure shown in the general formula (I) is as follows: The preparation process of the self-assembled hole transport material of the structure shown in the general formula (II) is as follows:

4. Use of the AIEgen type self-assembled hole transport material as claimed in claim 1 or 2, characterized in that: It is used to prepare inverse perovskite solar devices.

5. An inverse perovskite solar device based on the AIEgen type self-assembled hole transport material according to claim 1 or 2, characterized in that: It is used for the hole transport layer, which includes, from bottom to top, a transparent conductive substrate, a hole transport layer, an active layer, an electron transport layer and an electrode.

Citation Information

Patent Citations

  • Thermal activation delayed fluorescence material, synthesis method thereof and OLED (Organic Light Emitting Diode) device using thermal activation delayed fluorescence material

    CN103740359A

  • Squaraine-based ratio type fluorescent probe as well as preparation method and application thereof

    CN113563249A

  • Fluorescent dye fluorine boron compound with aggregation-induced emission and large Stokes shift and preparation method thereof

    CN114605452A

  • Self-assembled monomolecular layer hole transport material based on carbazole derivative and synthesis method and application thereof

    CN114716476A

  • Self-assembled monomolecular hole transport material, high-opening-voltage trans-perovskite battery and preparation method of self-assembled monomolecular hole transport material and high-opening-voltage trans-perovskite battery

    CN117946160A